2021
DOI: 10.3390/su13052932
|View full text |Cite
|
Sign up to set email alerts
|

Growing Biodiverse Urban Futures: Renaturalization and Rewilding as Strategies to Strengthen Urban Resilience

Abstract: How are our cities using nature-based solutions to confront the challenges posed by a warming climate, the loss of biodiversity and major resource depletion? This article discusses the opportunities and benefits of applying the concepts of regreening and rewilding of cities. The article engages with key sources and summarizes the background and development of regreening and nature-based solutions and important policies, concerns and perspectives of international and national organizations. It introduces the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 35 publications
1
19
0
2
Order By: Relevance
“…Our results of bird survey in SS and BS urban parks in Olomouc city can be considered only as indicative, because of more precise results should revealed method of mapping nest territories, which has not been used because of time limit. However, our result from line-transect method using for bird counting are in accordance with studies, which found out a close relationship between bird diversity and size area of urban parks (Lepczyk et al, 2017), presence of native features in urban green areas (Kümmerling & Müller, 2012;Lehmann, 2021), and proximity of urban parks to natural habitats out of city´s border (MacGregor-Fors & Ortega-Alvárez, 2011).…”
Section: Discussionsupporting
confidence: 91%
“…Our results of bird survey in SS and BS urban parks in Olomouc city can be considered only as indicative, because of more precise results should revealed method of mapping nest territories, which has not been used because of time limit. However, our result from line-transect method using for bird counting are in accordance with studies, which found out a close relationship between bird diversity and size area of urban parks (Lepczyk et al, 2017), presence of native features in urban green areas (Kümmerling & Müller, 2012;Lehmann, 2021), and proximity of urban parks to natural habitats out of city´s border (MacGregor-Fors & Ortega-Alvárez, 2011).…”
Section: Discussionsupporting
confidence: 91%
“…Birds are important components of urban landscapes, promoting ecosystem health [3]. They are also good indicators of the diversity of other animal groups and of habitat condition [4,5] because they are conspicuous, easy to quantify and quickly respond to habitat changes caused by urbanization [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Due to their informal and unrestricted character, rewilding cities provides stimulating natural elements which enhance the exploration and imagination skills of children (Henderson and Vikander, 2008 ; Gurholt and Sanderud, 2016 ; Bento and Dias, 2017 ). Also, rewilding means that nature takes its course and wildlife can flourish (Xie and Bulkeley, 2020 ; Lehmann, 2021 ). This solution may lead the opportunity to reintroduce lost biodiversity back into cities spaces and promote inter and intragenerational communication and a closer connection with nature, goals that can be associated with the Planetary Boundaries proposed by Steffen et al ( 2015 ), and its application to city level proposed by Hoornweg et al ( 2016 ).…”
Section: Minding the Gap: Children's Green Infrastructurementioning
confidence: 99%
“…Indeed, rewilding cities and enhancing biodiversity are essential processes for the promotion of CGI. This perspective implies a different approach than the one inspiring the creation of designated spaces for children, which tend to be highly structured, restricted and regulated, conditioning the exploration of space and the free play of children, especially for the most vulnerable ones (Lehmann, 2021 ). CGI, through its civic and participatory focus, aims to co-create natural areas by rewilding cities and creating open natural spaces that can be appropriated by children as their own, because children also participate in their design, together with adults and young people.…”
Section: Final Remarksmentioning
confidence: 99%